Adversarial attack defenses for neural networks - Puah, Yi Hao (Nanyang Technological University, 2024)
The widespread adoption of deep neural networks (DNNs) across various domains has led to the creation of high-performance models trained on extensive datasets. As a result, there is a growing need to protect the intellectual property of these models, leading to the development of various watermarking techniques.